THE USE OF ENGLISH SONGS TO IMPROVE ENGLISH STUDENTS’ LISTENING SKILLS - Eicha Afriyuninda; Lulud Oktaviani (Journal of English Language Teaching and Learning, 2021)
This study investigated students' listening skills using English songs. The reason for choosing this topic is based on the problem of listening ability. The purpose of this study was to determine the use of English songs to improve students' listening skills. The targets of this study were students in the fifth and seventh semester of the English Education study program in UniversitasTeknokrat Indonesia. 100 students participated in this study. This research method is qualitative. Data collection was carried out by distributing link questionnaires to 100 students who had taken listening courses. The results showed that the progress of students' listening skills mastery during the activity could be seen from the data analysis, the researchers used tabulated data. This result shows that English songs are effective in listening skills.